(untitled) (Medical Forum Monthly, 2024)
Objective: To ascertain the immunization status for hepatitis B in patients with chronic renal disease who are reliant on dialysis. Study Design: A cross-sectional study Place and Duration of Study: This study was conducted at the Nephrology, department. Peshawar's Lady Reading Hospital, from July 1, 2021, to December 31, 2021. Methods: Those receiving hemodialysis for chronic renal disease were included. The anti-HBS antibody titer in the patients' blood after three or four doses of the 20 microgram hepatitis B vaccine was used to validate the patients' hepatitis B vaccination status. A cut-off value of ≥10 IU/L was applied to the anti-HBS antibody titer. Results: 109 patients in all were enrolled. The patients' ages varied from 20 to 60. The patients' average age was 49.80 ± 5.245 years. The male to female ratio was 1.6:1. Of the patients, 81 (74.3%) got three doses of the vaccine, while 28 (25.7%) received four doses. 56 patients (51.4%) had vaccination records. Conclusion: CKD patients are less likely to develop ≥10IU/L of anti-HBS antibodies after hepatitis vaccination. Patients who receive vaccination in the early course of the disease are more likely to develop better response.